Canine melanoma: A review of diagnostics and comparative mechanisms of disease and immunotolerance in the era of the immunotherapies - Stevenson, Valentina B.; Klahn, Shawna; LeRoith, Tanya; Huckle, William R. (Frontiers in Veterinary Science, 2023)
Melanomas in humans and dogs are highly malignant and resistant to therapy. Since the first development of immunotherapies, interest in how the immune system interacts within the tumor microenvironment and plays a role in tumor development, progression, or remission has increased. Of major importance are tumor-infiltrating lymphocytes (TILs) where distribution and cell frequencies correlate with survival and therapeutic outcomes. Additionally, efforts have been made to identify subsets of TILs populations that can contribute to a tumor-promoting or tumor-inhibiting environment, such as the case with T regulatory cells versus CD8 T cells. Furthermore, cancerous cells have the capacity to express certain inhibitory checkpoint molecules, including CTLA-4, PD-L1, PD-L2, that can suppress the immune system, a property associated with poor prognosis, a high rate of recurrence, and metastasis. Comparative oncology brings insights to comprehend the mechanisms of tumorigenesis and immunotolerance in humans and dogs, contributing to the development of new therapeutic agents that can modulate the immune response against the tumor. Therapies that target signaling pathways such as mTOR and MEK/ERK that are upregulated in cancer, or immunotherapies with different approaches such as CAR-T cells engineered for specific tumor-associated antigens, DNA vaccines using human tyrosinase or CGSP-4 antigen, anti-PD-1 or -PD-L1 monoclonal antibodies that intercept their binding inhibiting the suppression of the T cells, and lymphokine-activated killer cells are already in development for treating canine tumors. This review provides concise and recent information about diagnosis, comparative mechanisms of tumor development and progression, and the current status of immunotherapies directed toward canine melanoma.